Effect of Landlockedness on Receiving Tourism Income in SAARC Countries - Dahal, Arjun Kumar; Budhathoki, Prem Bahadur (The Journal of Knowledge and Innovation, 2023)
This study looks into the economic-driven tourism growth hypothesis in the context of SAARC countries. It also investigates the effect of landlockedness on tourism income receipt. It is based on secondary data gathered from several World Bank Reports and economic surveys of respective countries. It made use of 169 data points from SAARC's eight member countries. The data from an unbalanced panel was used. It makes use of an exploratory and analytical research design. For the impact study of independent variables on dependent variables, descriptive statistics, panel unit root testing, panel quantile regression analysis, quantile process estimates, quantile slope equality test, and symmetric quantile test are used. The GDP has a positive impact on tourism income in SAARC countries. It is found that one percent increase in the median value of GDP, the tourism income is increased by 0.219 percent. The evidence has proved the economic-driven tourism growth hypothesis, particularly regarding SAARC countries. This highlights the need for tailored tourism initiatives aimed specifically at landlocked nations.